Clinicopathological Characteristics of Ocular Surface Squamous Neoplasia in National Eye Center, Cicendo Eye Hospital Bandung from 2019 to 2022 - Nia Nuraeni; Aminah, Hermin; Agustina, Hasrayati; Mardianty, Friska (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2025)
Introduction Ocular surface squamous neoplasm (OSSN) comprises a broad spectrum of dysplastic alterations of the squamous epithelium of the conjunctiva, ranging from conjunctival squamous intraepithelial neoplasm (CSIN) to squamous cell carcinoma (SCC). The aim of this study was to describe the clinicopathological characteristics of OSSN at National Eye Center, Cicendo Eye Hospital Bandung from January 2019 to December 2022. Methods We collected OSSN data from 2019 to 2022. The collected data were the patient's age, gender, education, occupation, laterality, clinical features, recurrence, and classification of tumor according to the 2022 WHO classification. Results: A total of 128 cases were collected. The most common tumor identified was SCC (48.4%), followed by CSIN with severe dysplasia (25%), moderate dysplasia, and mild dysplasia (14.8% and 11.7%, respectively). The average patient’s age was 53.1 years (M = 53.1, SD =16.9), predominantly males (68%), education completed elementary school (52.3%), and more patients worked outdoor (59.4%). The most common affected site was the left eye (53.9%), and the tumor located in the nasal region (78.1%) with clinical features is papilliform (64.1%). Conclusion OSSN was predominant in elderly male patients. The majority of cases were seen in the left eye, primarily in the nasal area. The majority of patients had completed elementary school and worked outdoors. Additionally, the clinical symptoms showed that most patients had papilliform. In patients with OSSN, SCC was the most common anatomical pathology discovered. Moreover, recurrence was higher in SCC cases.